THE INFLUENCE OF FINANCIAL LITERACY, RISK PERCEPTION, AND PRICE PERCEPTION ON INVESTMENT INTEREST IN THE CAPITAL MARKET AMONG STUDENTS IN SURABAYA - Lydya Nur Annisa; Nurul Azizah; Ricky Angga Ariska (Income, 2025)
This study analyzes the influence of financial literacy, risk perception, and price perception on students' investment interest. The research subjects are active students of the Faculty of Economics and Business in Surabaya, using a convenience sampling technique. Data was collected through Google Forms and analyzed using SPSS with 114 respondents. Each question was measured using a Likert scale. The results show that financial literacy, risk perception, and price perception have a positive and significant impact on students' investment interest. These findings emphasize the importance of financial understanding in boosting students' interest in investing.